METODE MOVING AVERAGE DAN METODE SUPPORT VECTOR MACHINE UNTUK PREDIKSI VARIABEL METEOROLOGI - Andita Dani Achmad (JTRISTE, 2018)
Meteorological variables predictions can help predict rainfall so that they can avoid losses from telecommunication network disruptions, determine the appropriate planting time and types of plants, and air transportation. In this study, the method used to predict meteorological variables of average wind speed is Moving Avarage and Vectot Machine Support by using the last 4 years data from the actual data for the Moving Average and while the last 5 years data from the actual data for the Support Vector Machine method. The results showed the results of the accuracy of the predictions for the average speed meteorological variables angina using the Support Vector Machine method and the Moving Average method each of 74.19% and 38.70%.